Mixed convection of micropolar fluid on a permeable stretching surface of another quiescent fluid - Nurazleen, Abdul Majid; Nurul Farahain, Mohammad; Abdul Rahman, Mohd Kasim; Sharidan, Shafie (Penerbit UTM Press, 2020)
In recent decades, micropolar fluid has been one of the major interesting research subjects due to the numerous applications such as blood, paint, body fluid, polymers, colloidal fluid and suspension fluid. However, the behavior of micropolar fluid flow over a permeable stretching surface of another quiescent fluid with a heavier density of micropolar fluid under the condition of mixed convection is still unknown. Thus, the current work aims to investigate numerically the mixed convection of micropolar fluid flow over a permeable stretching surface of another quiescent fluid. In this research, the similarity transformation is implemented to reduce the boundary layer governing equations from partial differential equations to a system of nonlinear ordinary differential equations. Then, this model is solved numerically using shooting technique with Runge-Kutta-Gill method and applied in Jupyter Notebook using Python 3 language. The behavior of micropolar fluid in terms of velocity, skin friction, microrotation and temperature are analyzed.